Depressive symptoms and harmful alcohol use in hepatitis C patients: prevalence and correlates - Machado, Danusa De Almeida; Silva, Giovanni Faria [UNESP]; Torres, Albina Rodrigues [UNESP]; Cerqueira, Ana Teresa de Abreu Ramos [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2014)
Introduction It is important to understand the characteristics and vulnerabilities of people who have hepatitis C because this disease is currently an important public health problem. The objective of this study was to estimate the prevalence of depressive symptoms and harmful alcohol use in patients with hepatitis C and to study the association between these outcomes and demographic, psychosocial and clinical variables. Methods This cross-sectional, descriptive and analytical study involved 82 hepatitis C patients who were being treated with pegylated interferon and ribavirin at a public university hospital. The primary assessments used in the study were the Alcohol Use Disorders Identification Test and the Beck Depression Inventory. Bivariate analyses were followed by logistic regression. Results The prevalence of depressive symptoms was 30.5% (n=25), and that of harmful alcohol use was 34.2% (n=28). Logistic regression analysis showed that individuals who were dissatisfied with their social support (OR=4.41; CI=1.00-19.33) and were unemployed (OR=6.31; CI=1.44-27.70) were at a higher risk for depressive symptoms, whereas harmful alcohol use was associated with the male sex (OR=6.78; CI=1.38-33.19) and the use of illicit substances (OR=7.42; CI=1.12-49.00). Conclusions High prevalence rates of depressive symptoms and harmful alcohol use were verified, indicating vulnerabilities that must be properly monitored and treated to reduce emotional suffering in this population.
Keywords: Hepatitis C; Depressive symptoms; Depression; Alcohol abuse; Alcohol harmful use